Neuroeconomía agraria familiar: aplicación de la Jerarquía de Patrones Neuronales Emocionales en el sector de fibra de alpaca y papa nativa en Perú - Zúñiga Aguilar, Isaac (2022)
This study aims to analyze the neuroeconomic decision-making of small producers of alpaca fiber and native potato considering the Neural Pattern Hierarchy Theory and the Temporal Memory Model. The aim is to measure the impact on the correlation level of holistic competencies of innovation in The learning process based on entrepreneurship. To achieve this, experimental, transactional, correlational, and descriptive research was conducted with a sample of 88 individuals. A methodology for aligning emotional neural patterns was applied. The results show that (H1:Y0 > Y1) emphasizing alpaca fiber.